Evaluation of the Clinical Pattern of Limb Amputations in Patients with Electrical Burns During the Pandemic COVID-19 - Avila, Alan Guillermo Zavaleta; Madrid, Paul Robledo; Palafox, Mario Velez (British Journal of Healthcare and Medical Research, 2026)
Burns caused by electricity, are devastating injuries, can cause loss of life, The epidemiological pattern of this type of injury increased during the covid-19 pandemic. The objective of this study was to evaluate the clinical pattern of limb amputation in patients with electrical burns treated at CENIAQ from March 2020 to February 2023 This is a prospective study of routine medical practice with convenience sampling, for 36 months. One of the epidemiological and social phenomena during the COVID-19 pandemic was the incorporation of personnel without adequate preparation for high-risk tasks, conditioning devastating injuries that required amputation of one or more limbs